On some applications of the singularity method - Zapryanov, Zapryan; Markov, Nikolay (Ann. Sofia Univ. Fac. Math. and Inf., 1996)
The hydrodynamics of low Reynolds number flows plays an important role in the study of suspension machanics, clloid science and membrane physiology. In the present paper once again (now vie the singularity method) some steady viscous flows in the presence of rigid or fluid particles are examined. The flows are represented in terms of fundamental solutions to the governing Stokes equations, including Stokeslets, degenerated quadrupoles, Stokesons and some other multipoles. The problems considered are 1) flow due to the translation or rotation of a rigid spherical particle; 2) a translating spherical drop in a viscous quiescent fluid; 3) small deformations of a fluid particle in a general linear flow.